1992
DOI: 10.1002/art.1780350710
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of peripheral blood mononuclear cells to vascular endothelium in patients with systemic sclerosis (scleroderma)

Abstract: Objective. Perivascular infiltrates in skin, subcutaneous tissue, and internal organs are a characteristic feature of early systemic sclerosis (SSc). We studied the first step of migration of peripheral blood mononuclear cells (PBMC) through the vessel wall to the extravascular space, i.e., adhesion of PBMC to endothelial cells (EC), in patients with various forms of SSc (limited scleroderma, diffuse scleroderma, and the transitional form).Methods. Radioisotope-labeled patient PBMC were coincubated with umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…In vitro studies have found that PBMCs from SSc patients adhere abnormally to endothelial cells with an overall reduction in binding but with enhanced binding of a subfraction of activated cells; this is consistent with the concept that lymphocyte traffic across endothelium is chronically upregulated in SSc lesions and leads to a depletion of circulating responsive cells (22). There is now considerable recent evidence for enhanced expression of adhesion molecules on endothelium in SSc patients, both within lesions and at clinically uninvolved sites (23)(24)(25)(26), together with increased circulating levels of soluble forms of adhesion molecules and other markers of endothelial activation or damage, including vWF, endothelin-1, and thrombomodulin (27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionsupporting
confidence: 78%
“…In vitro studies have found that PBMCs from SSc patients adhere abnormally to endothelial cells with an overall reduction in binding but with enhanced binding of a subfraction of activated cells; this is consistent with the concept that lymphocyte traffic across endothelium is chronically upregulated in SSc lesions and leads to a depletion of circulating responsive cells (22). There is now considerable recent evidence for enhanced expression of adhesion molecules on endothelium in SSc patients, both within lesions and at clinically uninvolved sites (23)(24)(25)(26), together with increased circulating levels of soluble forms of adhesion molecules and other markers of endothelial activation or damage, including vWF, endothelin-1, and thrombomodulin (27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionsupporting
confidence: 78%
“…Previous studies have shown that SSc peripheral blood mononuclear cells and SSc dermal fibroblasts are hyperadhesive 19. Here we found that JAM-A is overexpressed on SSc dermal fibroblasts and mediates the adhesion of myeloid U937 cells to both SSc dermal fibroblasts and proximal and distal SSc skin.…”
Section: Discussionsupporting
confidence: 52%
“…JAM‐A and JAM‐C may therefore contribute to the proadhesive phenotype of dermal ECs, inflammatory/immune cells, and fibroblasts and participate in the complex intercellular cross‐talk among these different cell types in early‐stage SSc. Indeed, previous studies have shown that SSc ECs, peripheral blood mononuclear cells, and activated fibroblasts are hyperadhesive (8–13, 37, 38). The increased expression of JAMs on blood vascular ECs from patients with early‐stage SSc may mediate the influx of inflammatory/immune cells into the dermis, where they may stimulate fibroblasts by both direct contact and the release of profibrotic mediators (1, 8).…”
Section: Discussionmentioning
confidence: 99%